Radiologic Changes in Patients with Temporomandibular Joint Hypermobility: A Cone Beam Computed Tomography Study - M. Akif Sümbüllü; Nihat Kiliç; Songül Cömert Kiliç (Atatürk University, 2024)
Objective: This study aimed to evaluate radiologic changes in patients with temporomandibular joint hypermobility using Cone Beam Computed Tomography (CBCT). Methods: This retrospective study included the first-visit CBCT images of 41 patients (mean age, 32.83 ± 13.63 years) treated for TMJ hypermobility. CBCT images of sixty-eight joints with TMJ hypermobility taken by using NewTom 3G were evaluated. Condylar erosion, sclerosis, hypoplasia, and flattening were assessed on the CBCT images. In addition, flattening of articular eminence, subchondral cyst, and pneumatization were also evaluated in the images. Descriptive statistical analysis was performed on the data. Results: Degenerations were observed in 47 joints (%69.11). Condylar erosion was the most common finding of TMJ hypermobility (43 of 68 joints, 63.2%). Other frequent condylar bony changes were condylar osteophyte (32 joints, 47.1%), sclerosis (8 joints, 11.8%), hypoplasia (8 joints, 11.8%), and flattening (6 joints, 8.8%). The flattening of articular eminence (3 joints, 4.4%) and subchondral cyst (3 joints, 4.4%)), and) were other findings on CBCT images. One joint showed a bifid condyle and pneumatization (1.5 %) (Table 1). Conclusion: The present study showed that two of three patients with TMJ hypermobility had joint degenerations. Condylar erosion and osteophyte are the most common degenerations observed in these patients. Therefore, CBCT is recommended for the diagnosis and management of TMJ hypermobility. Keywords: Cone beam computed tomography, TMJ hypermobility, Diagnosis Temporomandibular Eklem Hipermobilitesi Olan Hastalarda Radyolojik Değişiklikler: Koni Işınlı Bilgisayarlı Tomografi Çalışması ÖZ Amaç : Bu çalışmada temporomandibular eklem hipermobilitesi olan hastalarda Koni Işınlı Bilgisayarlı Tomografi (CBCT) kullanılarak radyolojik değişikliklerin değerlendirilmesi amaçlandı. Yöntemler: Bu retrospektif çalışmaya, TME hipermobilitesi nedeniyle tedavi edilen 41 hastanın (ortalama yaş, 32,83 ± 13,63 yıl) ilk ziyaret KIBT görüntüleri dahil edildi. TME hipermobilitesi olan 68 eklemin NewTom 3G kullanılarak alınan KIBT görüntüleri değerlendirildi. KIBT görüntülerinde kondiler erozyon, skleroz, hipoplazi ve düzleşme değerlendirildi. Ayrıca görüntülerde eklem eminensinde düzleşme, subkondral kist ve pnömatizasyon da değerlendirildi. Veriler üzerinde tanımlayıcı istatistiksel analiz yapıldı. Bulgular : 47 eklemde (%69,11) dejenerasyon gözlendi. Kondiler erozyon, TME hipermobilitesinin en sık görülen bulgusuydu (68 eklemden 43'ü, %63,2). Kondiler osteofit (32 eklem, %47,1), skleroz (8 eklem, %11,8), hipoplazi (8 eklem, %11,8) ve düzleşme (6 eklem, %8,8) diğer sık görülen kondiler kemik değişiklikleriydi. Artiküler eminenste düzleşme (3 eklem, %4,4) ve subkondral kist (3 eklem, %4,4) ve) KIBT görüntülerindeki diğer bulgulardı. Bir eklemde bifid kondil ve pnömatizasyon (%1,5) görüldü (Tablo 1). Sonuç: Bu çalışma TME hipermobilitesi olan üç hastadan ikisinde eklem dejenerasyonunun olduğunu gösterdi. Bu hastalarda en sık görülen dejenerasyonlar kondiler erozyon ve osteofittir. Bu nedenle TME hipermobilitesinin tanı ve tedavisinde KIBT önerilmektedir. Anahtar Kelimeler : Konik ışınlı bilgisayarlı tomografi, TME hipermobilitesi, Tanı